The effect of classroom rank on learning throughout elementary school: Experimental evidence from Ecuador - Pedro Carneiro; Yyannú Cruz Aguayo; Francesca Salvati; Norbert Rüdiger Schady (Inter-American Development Bank (IDB), 2023)
We study the impact on learning of a child's rank in the classroom using a unique experiment from Ecuador. Within each school, students were randomly assigned to classrooms in every grade between kindergarten and 6th grade.Therefore, two students with the same ability can have different classroom ranks because of the (random) peer composition of their classroom. To isolate the impact of rank from other peer influences we include classroom fixed effects. Children with higher classroom rank at the beginning of the academic year have significantly higher math test scores at the end of that grade. Classroom rank in math, not language, drives our results. The impact of classroom math rank is larger for younger children, and grows substantially over time. Exogenous changes in classroom rank in math also improve executive function, child happiness, and teacher perceptions of student ability.
Keywords: I20; 330; Classroom rank; test scores